دراسة تطور الإيرادات الضريبية في سورية (2000-2009) والتنبؤ بحصيلة هذه الإيرادات (2010-2015) انطلاقاً من بيانات قطع حسابات الموازنات العامة للدولة - النعيمي قاسم; العدي إبراهيم; رجوب ابتسام علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
نتناول في هذا البحث تطور الإيرادات الضريبية في سورية انطلاقاً من بيانات قطع حسابات الموازنات العامة للدولة للأعوام 2000-2009، وباستخدام البرنامج الإحصائي SPSS قمنا بالتنبؤ للفترة المقبلة (2010-2015) لإجمالي الضرائب ونسبة مساهمتها في إجمالي الإيرادات، كما قمنا بالتنبؤ لكل من الضرائب المباشرة، الضرائب غير المباشرة، الضرائب على الدخل، الضرائب على رأس المال، الضرائب على الإنفاق ونسبة مساهمة كل منها في إجمالي الضرائب والرسوم، بهدف الوصول إلى مجموعة من النتائج والمقترحات التي تسهم برفع مستوى النظام الضريبي السوري، فمع رفع شعار التطوير والتحديث في خطة الرئيس بشار الأسد، وبالتزامن مع اعتماد نظام السوق الاجتماعي وما تشهده سورية من انفتاح اقتصادي على المستوى العربي والدولي بات جلياً الحاجة الماسة لتطوير النظام الضريبي القائم والانتقال به إلى مراحل أكثر تقدماً بما يتناسب مع الواقع الاقتصادي والاجتماعي القائم وبما يفي بمتطلبات التنمية. In this research we will deal with the tax income in Syria through cuts of the accounts of the general budget of the State 2000-2008, and by using the statistical program SPSS, we estimate for (2010-2015) the total tax and the percentage of its contribution to total revenues, and we estimated all of the direct taxes, indirect taxes, income taxes, taxes on capital, taxes on expenditure and the percentage of each one’s contribution to the total taxes and fees to access to a set of conclusions and proposals that contribute to raising the level of the Syrian tax system Raising the slogan of development and modernization in President Bashar al-Assad’s plan as well as in conjunction with the adoption of the Social Market Economy and what Syria witnesses of economic openness on the Arab and international level, it became clear that we are in urgent need for the development of the existing tax system and move it to more advanced stages to commensurate with the existing economic and social reality and meet the requirements of development.